PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MELALUI MEDIA CERITA BERGAMBAR PADA ANAK KELOMPOK B DI BA A’ISYIYAH SIDOHARJO - Devi Nur Utami; Ida Yeni Rahmawati; Muhibbudin Fadhli (Universitas Muhammadiyah Ponorogo, 2020)
The objectives of this classroom action research is to describe and explain the process of learning to begin with through picture stories in BA ‘Aisyiyah Sidoharjo. This type of research is collaborative classroom action research. The research model used is Kemmis and Mc. Taggart. The subjects of this class action research were group B students in BA ‘Aisyiyah sidoharjo, amounting to 17 children consisting of 10 boys and 7 girls. The object of this research is the skill of beginning reading in children through pictorial story media The data analysis technique was carried out with qualitative and quantitative descriptive. The results of research on the beginning of reading activities showed an increase, it can be seen from the results of the initial activity before the action showed 5.89%, an increase of 17.63% in Cycle I to 23.52%, and an increase of 65% so that it reached 88 , 23% in Cycle II. Based on the results of this study, it can be concluded that the activity of learning to begin reading with picture stories can improve the skills of beginning reading in children. Keywords: Early Ready, Picture story, Early Childhood